MUTU MANISAN KERING BONGGOL NANAS (Ananas comosus L. Merr) TERHADAP PENILAIAN SENSORI - Lorenza, Diana; Hamzah, Faizah; Rahmayuni, Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aim ofthis research weretreatment withconcentration of citric acid and soaking time on quality dried sweetened pineapple core. A complete random design with two factors and three replications was applied in this research. The first factor wascitric acid concentration 0.1%, 0.15% and 0.2% and second factor is soaking time 36 hours, 45 hours and 54 hours. The design response was usedDuncan’s New Multiple Range Test (DNMRT) the level 5%. Parameters observed were the evaluation sensory of description and hedonic (colour, flavor, taste, texture and overall assessment). Treatment with concentration of citric acid and soaking time have an effects to evaluation sensory of description and hedonic on colour, flavor, tastebut not have an effect totexture and overall assessment. The best treatment of dried sweetened pineapple core was obtained 0.15% concentration of citric acid and 12 hours soaking time with color is dark yellow (score 2.53) and preferred (score 4.10), flavorful pineapple (score 4.26) and preferred (score 4.21), quite sweet and sour of taste (score 3.53) and preferred (skor 4.21), hard textured (score 2.40) and quite like (score 3.26) and overall assesment is preferred (score 4.32). Keywords:citric acid, soaking time, pineapple core, dried sweetened